Cervical cancer screening in high-altitude areas in China: A large cross-section study of 25,173 women in northern Tibet - Wang, Qimin; He, Yingying; Long, Fang; Li, Chaoran; Shen, Zhuowei; Guo, Dongxing; Zhaxi, Duoji; Bumu, Lamu; Hua, Zhengyu; Sun, Zhigang; Jiang, Nan; Han, Xu; et al. (Frontiers in Oncology, 2022)
Background Cervical cancer is widely concerned due to its high incidence rate and mortality. But there was no large-scale cervical cancer screening program in City of Nagqu, north of Tibet.Therefore, we investigated the recent HPV prevalence and genotype distribution among females in Nagqu to reveal cervical cancer and its precursors morbidity. Methods Totally 25,173 were recruited to receive the HPV genotype testing between June to December 2019.Women with HPV 16 or/and 18 infection received coloscopic and histological examination and women sufferring from other hrHPV infection received cytology test to derermine whether receive further coloscopic and histological examination for diagnosis. Results Total HPV infection rate in Women of Nagqu was 13.42%. Within the 25,173 women in the study, 999 (3.97%) were HPV 16/18 positive, 2, 379 (9.45%) were other hrHPV positive, the other 21, 795 (86.58%) women were HPV negative. 5 most common HPV subtypes in Nagqu people were HPV 16, 58, 31, 18, 52, this first genotypes accounted for more than 60% percent of all the infection. There seemed to be a positive correlation between HPV prevalence rate and altitude elevation: the higher the altitude, the more the HPV prevalence rate of women. Conclusion Our survey provided an overall perspective of HPV genotype infection and cervical lesions in women in North of Tibet. The data could not only provide useful information in the treatment of cervical lesions, but also have great value in the primary and secondary prevention measures for women living there.